Influence of microwave energy on structural and photoluminescent behavior of CaTiO3 powders - Marques, V. S.; Cavalcante, L. S. [UNESP]; Sczancoski, J. C. [UNESP]; Volanti, D. P. [UNESP]; Espinosa, J. W. M. [UNESP]; Joya, M. R.; Santos, M. R. M. C.; Pizani, P. S.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2008)
Calcium titanate, CaTiO3 powders were prepared by the polymeric precursor method and annealed at different temperatures for 2 h in a conventional furnace and for 30 min on an adapted microwave oven. The effect of microwave energy on structural and photoluminescent behavior of CaTiO3 powders was investigated by means of X-ray diffraction, micro-Raman scattering and photoluminescence measurements. The results of the CaTiO3 powders processed in the microwave oven showed a high structural organization compared to conventional treatment. (C) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: microwave; calcium titanate; structural order-disorder; photoluminescence